A critical discourse analysis of media coverage on Moroccan Arabic in textbooks and Arabic language acquisition in Morocco - Sakina M. Alaoui (Discover Education)
Abstract This paper examines the linguistic situation in Morocco, with a particular focus on Arabic. The Ministry of Education’s approval of a grade two Arabic textbook that employs dialectal Arabic (Darija) words instead of Standard Arabic, which is the usual writing mode, created fierce controversy in the social and political scene between the defenders of the use of Darija in textbooks and its detractors. To establish the underlying context of this polemic situation, it is vitally important to understand the complexity of the linguistic scape in the region. Thus, the present study offers an overview of this linguistic landscape, showcasing its Arab, Berber and European linguistic and cultural influences. It focuses on the Arabic diglossic situation that exists in the region and that gave rise to polarized linguistic ideologies and language policies, both of which have resulted in social and educational turmoil. This turmoil has been reported and debated in news media. The present paper analyses a newspaper article which reported the news using a critical discourse analysis (CDA) approach in an attempt to reveal how the discursive practices used in the text, such as metonymy and indexicality, endorse the Ministry’s stance and legitimize it, thus perpetuating an interpretation which supports their interests while obscuring and delegitimising the other side’s position. These findings reveal the shift that occurred in the Ministry of Education’s stance toward Darija, from the preference of Modern Standard Arabic as the proper language of instruction as opposed to the vernacular that interferes with education competency, to the integration of Darija in written texts and its acceptance as a pedagogical tool for effective language acquisition. The implication of these findings is twofold: They underscore the need for a more pragmatic approach to language policy, implementing transitional bilingual education. More importantly, they support the recommendation that strong government intervention to change attitudes in all levels of society is a pressing need, without which a change in language policy will be ineffectual.